Effects of long-term football training on the expression profile of genes involved in muscle oxidative metabolism. Issue 1 (February 2015) - Alfieri, A.; Martone, D.; Randers, M.B.; Labruna, G.; Mancini, A.; Nielsen, J.J.; Bangsbo, J.; Krustrup, P.; Buono, P.
Abstract: We investigated whether long-term recreational football training affects the expression of health-related biochemical and molecular markers in healthy untrained subjects. Five untrained healthy men trained for 1 h 2.4 times/week for 12 weeks and 1.3 times/week for another 52 weeks. Blood samples and a muscle biopsy from the vastus lateralis were collected at T0 (pre intervention) and at T1 (post intervention). Gene expression was measured by RTqPCR on RNA extracted from muscle biopsies. The expression levels of the genes principally involved in energy metabolism (PPARγ, adiponectin, AMPKα1/α2, TFAM, NAMPT, PGC1α and SIRT1) were measured at T0 and T1. Up-regulation of PPARγ ( p  < 0.0005), AMPKα1 ( p  < 0.01), AMPKα2 ( p  < 0.0005) and adiponectin was observed at T1 vs T0. Increases were also found in the expression of TFAM ( p  < 0.001), NAMPT ( p  < 0.01), PGC1α ( p  < 0.01) and SIRT1 ( p  < 0.01), which are directly or indirectly involved in the glucose and lipid oxidative metabolism. Multiple linear regression analysis revealed that fat percentage was independently associated with NAMPT, PPARγ and adiponectin expression. In conclusion, long-term recreational football training could be a useful tool to improve the expression of muscle molecular biomarkers that are correlated to oxidative metabolism in healthy males.